2017
DOI: 10.1111/apt.13934
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive enteral nutrition provides an effective bridge to safer interval elective surgery for adults with Crohn's disease

Abstract: Exclusive enteral nutrition frequently down-stages the need for surgery in patients presenting with stricturing or penetrating complications of Crohn's disease; it is associated with a reduction in systemic inflammation, operative times and the incidence of post-operative abscess or anastomotic leak. Further trials are needed to elucidate how exclusive enteral nutrition may improve operative outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
140
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(157 citation statements)
references
References 35 publications
(76 reference statements)
3
140
2
3
Order By: Relevance
“…Heerasing et al [58] retrospectively revised 51 patients treated with preoperative EEN after nutritional assessment. Thirteen patients (25%) ended up not requiring surgery.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Heerasing et al [58] retrospectively revised 51 patients treated with preoperative EEN after nutritional assessment. Thirteen patients (25%) ended up not requiring surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to their respective controls, patients under preoperative EEN achieved significantly lower levels of preoperative inflammatory markers in three of the reviewed studies [58-60], in two of which with concomitant increases in serum albumin values [59, 60]. The two studies with the greatest number of patients found preoperative EEN to be an independent factor against postoperative infectious and non-infectious complications [57] and against anastomotic leaks or abscesses [58]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported in western countries that partial enteral nutrition was showed to be an effective option for maintaining remission and perioperative management [31, 32]. ESPEN guideline recommended the use of elemental nutrition (EN) in CD patients with symptomatic intestinal strictures or stenosis [33].…”
Section: Discussionmentioning
confidence: 99%